The Indian Ocean nodule field : geology and resource potential - Mukhopadhyay, Ranadhir (Elsevier, 2018)
The Indian Ocean Nodule Field: Geology and Resource Potential, Second Edition, provides a view of the most recent studies along with classical theories starting from the 1960s. New concepts, hypotheses and critical appreciation of the state-of-the-art knowledge on nodule formation and resource management are featured in this new edition. The economy of the Indian Ocean has vast potential and yet it is one of the least studied oceans. Garnering economic advantage out of mineral resources from deep oceans has been a long cherished dream for the mining community. The availability of 5-metal rich polymetallic (manganese) nodules in specific areas of the Indian Ocean has lured researchers to discover more about their processes of formation, growth, distribution and enrichment. Collates, discusses and succinctly presents voluminous and scattered information from various books and journals for easy understanding and disseminationFeatures two new chapters: statistical modeling of the formation, growth, distribution and metal enrichment of nodules; and biogeochemistry of the Central Indian Ocean BasinIncludes an assessment of Indian Ocean nodules, one of the least studied oceans in comparison to samples analyzed from the world's oceans.